Everybody wants to rule the world surviving and thriving in a World of digital giants - Wang, Ray. (Michigan Brilliance Audio, 2021)
Drawing on considerable original research and case studies from Wang's acclaimed firm, Constellation Research, this groundbreaking guide reveals which kinds of companies will thrive and which will get crushed by the powerful forces now at work.